Heterogeneous material properties—as inferred from seismic attenuation—influenced multiple fault rupture and ductile creep of the Kaikoura Mw 7.8 earthquake, New Zealand. Issue 2 (19th July 2021) - Eberhart-Phillips, Donna; Ellis, Susan; Lanza, Federica; Bannister, Stephen
SUMMARY: The 2016 M w 7.8 Kaikoura, New Zealand, earthquake occurred along the eastern margin of the transition region between active subduction in the North Island and oblique collision in the South Island. To infer crustal properties, we imaged Q (1/seismic attenuation) by combining selected M > 3.5 aftershocks with data from previous Q models. For 158 distributed aftershocks, we fit spectral decay on temporary stations and all Geonet stations, providing 6194 t * p and 19 497 t * s . Considering the varied rheology and faults, we also used 2.5-D numerical models to study ductile strain development. The complex earthquake ruptured an ∼180-km-long zone of multiple faults, which involved jumping around the complicated eastern end of the Hope fault, without significant slip on the Hope fault. The Qs and Qp results show features in the upper and lower crust which correlate to the distribution and types of fault rupture. This earthquake involved numerous faults over a region of greywacke crust, where the underlying high Q Cretaceous slab is about 30-km depth. It initiated with ∼5-m slip on the Humps fault in a region of background seismicity and low Q lower crust, adjacent to the Hope fault. The central region near Kaikoura shows a high Q crustal block, which appears to have inhibited rupture; as the rupture progressed over several small faults to jump offshore of the apparently strong block. Underlying the Kaikoura greywacke crust, below 20-km depth, there is a 40-km-long region of increased Vp, Qs and gravity, which likely represents an intraplate plutonic complex emplaced into the Hikurangi Plateau, forming an elevated section which influences deformation. In the northern section, in a region with relatively uniform moderate to low Q, the earthquake evolved into the relatively continuous ∼80-km-long major rupture along the Jordan, Kekerengu and Needles faults, with ∼6–20 m dextral slip at depth and surface displacements of ∼10 m dextral and ∼2 m vertical. The northern progression of the rupture stopped when it approached an abrupt change to high Q crust across Cook Strait. At 20–30-km depth northwest of the rupture, deeper zones with low Q are consistent with regions of distributed ductile shear and creep where the observed afterslip may have occurred, where the underlying slab is 25–40 km deep. The numerical model shows that ductile deformation localizes in this area of lower crust above the relatively strong slab, connecting outer faults (Kekerengu) to inland faults (Clarence, Awatere, Wairau), and demonstrates that no subduction thrust is required under the Marlborough region.